Grip Strength Impairment and Neuropathic-Like Pain as Predictors of Functional Decline in Hand Osteoarthritis - Mathieu S; Fayet F; Salembien MH; Rodere M; Soubrier M; Tournadre A (Open Access Rheumatology: Research and Reviews)
Sylvain Mathieu,1,2 Françoise Fayet,2 Marie-Hélène Salembien,2 Malory Rodere,2 Martin Soubrier,2 Anne Tournadre2 1Université Clermont Auvergne, CHU Clermont-Ferrand, INSERM, Neuro-Dol, Clermont-Ferrand, 63000, France; 2Service de Rhumatologie, CHU Clermont-Ferrand, Clermont-Ferrand, 63000, FranceCorrespondence: Sylvain Mathieu, Service de Rhumatologie, CHU Clermont-Ferrand, Clermont-Ferrand, 63000, France, Tel +0033473751488, Fax +0033473751489, Email smathieu@chu-clermontferrand.frObjective: (1) To define the factors associated with pain, functional limitation, grip strength (GS), sarcopenia and quality of life (QoL) in hand osteoarthritis (HOA) patients and (2) to compare the characteristics of HOA patients with or without neuropathic-like pain.Methods: The clinical parameters (numeric rating scale (NRS) for pain, Functional Index for HOA (FIHOA), GS, QoL, and sarcopenia) were completed by hand radiographs and biological analysis. A neuropathic-like pain was retained if the DN4 score was ≥ 4/10. We performed a cross-sectional study comparing the patients’ characteristics using the Student’s t-test or Chi-square. The relation between clinical parameters and others was studied with Spearman correlation or logistic regression.Results: 110 hOA patients (mean age of 66.2 years and 89% of women) were included. Twenty-eight HOA patients presented a comorbidity (25.7%: 28/109) and eight had sarcopenia (8/63: 12.7%). Hand GS was negatively associated with age (r=− 0.23; p=0.049), higher in men (p=0.003), and lower in erosive disease (p=0.03). Sarcopenia significantly correlated with higher pain intensity (p=0.046), greater functional impairment (FIHOA, p=0.01), and lower QoL (p=0.03). The presence of comorbidity altered the QoL (p=0.047). Depression was significantly associated with all clinical parameters, except GS. Sixty HOA patients had neuropathic-like pain (56.0%); these were younger, had a higher FIHOA, and reported more night awakening and morning stiffness; however, C-reactive protein (CRP) levels were not different.Conclusion: Neuropathic-like pain and sarcopenia exacerbate functional decline in HOA, highlighting the need for targeted interventions beyond conventional analgesics.Keywords: hand osteoarthritis, neuropathic-like pain, grip strength, sarcopenia